Pak Wan Daging Bako / Nor Syafiqah Mohd Azwan - Mohd Azwan, Nor Syafiqah (2021)
Pak Wan Daging Bako provides product that can give a new experience for our customers in terms of taste. Our product offers affordable and reasonable price to all of our beloved customers. Also, we provide cash on delivery for our customer when they purchase our products. Our target market is a group of people who are looking difference taste in food. All of our ingredients are premium and the meat itself is high quality. Our target customer would be around Langkawi as our business was based in here. At the moment, this business was only owned and work by Nor Syafiqah bt Mohd Azwan. Our business use Facebook Page and WhatsApp platform for marketing and accepting order. We use teaser post, soft sell and hard sell as our marketing posting on Facebook. Last but not least, we eager to get customers satisfaction and to become preferred Daging Bako in town.